CCD photometric search for peculiar stars in open clusters. VII. Berkeley11, Berkely 94, Haffner 15, Lyngå 1, NGC 6031, NGC 6405, NGC 6834 and Ruprecht 130 - Paunzen, E. (2003)
We have investigated 1008 objects in the area of five intermediate age open clusters (NGC 2099, NGC 3114, NGC 6204, NGC 6705 and NGC 6756) via the narrow band δa-system. The detection limit for photometric peculiarity is very low (always less than 0.009 mag) due to the high number of individual frames used (193 in total). We have detected six peculiar objects in NGC 6705 and NGC 6756 from which one in the latter is almost certainly an unreddened late type foreground star. The remaining five stars are probably cluster members and bona fide chemically peculiar objects (two are λ Bootis type candidates). Furthermore, we have investigated NGC 3114, a cluster for which already photoelectric δa-measurements exist. A comparison of the CCD and photoelectric values shows very good agreement. Again, the high capability of our CCD δa-photometric system to sort out true peculiar objects together with additional measurements from broad or intermediate band photometry is demonstrated.